Short and Long Run Dynamic Common Correlation Effects of External Capital Inflow on Economic Growth in SSA Countries - Dinga, Gildas Dohba; Fonchamnyo, Dobdinga Cletus; Nginyu, Giyoh Gideon; Njuh, Chuo Joshua (Asian Journal of Economic Modelling, 2020)
The socio-economic effects of shock in one country produce a spillover effect on other economies given the global village nature of the world today. Current economic analyses have tended to adopt methodologies that treat cross sectional dependence in analysing macroeconomic phenomena. We employ the novel dynamic common correlation effect technique of Chudik and Pesaran (2015) that accounts for cross sectional dependence to examine the short and long run effects of different sources of external capital (foreign direct investment (FDI), official development aid (ODA) and external debt) on economic growth within 36 Sub Saharan African countries between 1995-2018. The result indicates a negative effect of external debt and ODA on economic growth in both the short and long run but it’s only statistically significant in the short run. FDI is positive but only statistically significant in the short run. Disparity is noticed in the results especially in the long run when the panel is sub divided into lower and middle income countries. ODA and FDI exert positive long run effect in low income countries but negative in middle income countries. Meanwhile debt is negative for both income groupings.